Adverse events and stroke prevention by interventional left atrial appendage occlusion in patients with low CHA2DS2-VASc score: results from the multicenter German LAARGE registry : original studies - Fastner, Christian; Brachmann, Johannes; Lewalter, Thorsten; Zeymer, Uwe; Sievert, Horst; Ledwoch, Jakob; Geist, Volker; Hochadel, Matthias; Schneider, Steffen; Senges, Jochen; Akın, Ibrahim; Ansari, Uzair (Catheterization and cardiovascular interventions, 2022)
Background Interventional left atrial appendage occlusion (LAAO) is routinely performed in patients with nonvalvular atrial fibrillation and contraindications to standard anticoagulation. Aims We investigated its role in patients at low stroke risk, and compared the effectiveness and safety in patients with low versus high risk. Methods LAARGE is a prospective registry depicting the clinical reality of LAAO. LAAO was conducted with different standard commercial devices, and follow-up period was 1 year. Patients with started procedure and documented CHA2DS2-VASc score were selected from the whole database. Results A total of 638 patients from 38 centers were divided into CHA2DS2-VASc score ≤2, i.e., low-risk group (10.2%), and >2, i.e., high-risk group (89.8%). The latter had a pronounced cardiovascular risk profile and preceding strokes (0% vs. 23.9%; p < 0.001). Implantation success was consistently high (97.6%), frequencies of intrahospital major adverse cardiac and cerebrovascular events (0% vs. 0.5%) and other major complications (4.6% vs. 4.0%) were low (each p = not significant [NS]). Numerous moderate complications were also observed in the low-risk patients (12.3% vs. 9.4%; p = NS). Frequencies of nonfatal strokes (0% vs. 0.7%) and severe bleedings (0% vs. 0.7%) were low (each p = NS). In a specific analysis, patients at very high risk of stroke (i.e., CHA2DS2-VASc score >4) did not have increased rates of complications or nonfatal strokes in the first year after the procedure. Conclusions Low-risk patients had no nonfatal strokes and major bleedings within 1 year after hospital discharge but had unexpectedly high rates of moderate procedural complications. The indication in these patients should be strictly defined based on an individual benefit-risk assessment.